Temporal conceptual models for contaminated complex site management, based on a remediation case of chlorinated solvent commingled plumes in weathered and fractured bedrock - Hart, Sasha Tom (2023)
Contaminated properties and regions, mainly abroad, have been named as Complex Areas due to the existence of technical or non-technical challenges that require atypical longer timelines and management for their restoration. In the United States of America 9.5% of all their identified contaminated sites (126 thousand) have been considered as complex from a hydrogeologic and contaminant perspective. In Europe, continental initiatives were developed to recognize and learn from the complex, large and prominent brownfields. In Brazil, the State of Sao Paulo has classified 18 sites as Critical Areas, a type of Complex Area, representing 0.27% of the total amount (6.6 thousand) of currently know contaminated areas. This research main objective is to evaluate Complex Area management and contribute with its enhancement, based on the development of a more clear and holistic conceptual site model for a remediated site in São Paulo, Brazil, that presented commingled plumes including within former abstraction wells in fractured bedrock. Its complex challenges were evaluated and detailed spatially and temporally with the development of a Temporal Conceptual Model, defined in this study. Several tools were applied, including Compound Specific Isotopic Analysis (for carbon and chlorine) with geoforensic approach, bedrock logging and implicit modelling. Prior to full scale remediation of the study area, an off-site source area with unknown history and limited access presented lower 13C values (-6.5 to -1.8 for 1,2-Dichloroethane) and distinct signature than that determined for the downgradient on-site source area (+8.6 to +20.0). Intermediate 13C values for 1,2-Dichloroethane were identified further downgradient, within a commingled plume configuration. After bioremediation and thermal treatment, isotopic fractionations were identified. In the former main abstraction well concentrations have continuously dropped over the last 9 years, to below potability limits. Multiple lines of evidence and the site rehabilitation (formally agreed after 22 years management) confirmed the interventions in the area benefited from the using the Temporal Conceptual Model and aspects of Adaptive Management for Complex Areas, such as the definition of intermediate objectives, continuous refinement of the conceptual model and remediation adjustments. In Brazil and other countries there are possibly many other sites similar to this area, with technical and non-technical challenges that prevent meeting objectives in typical timeframes. It is recommended that Complex Areas shall be further identified and managed following international recommendations, while also contemplating local considerations and adaptations, such as: 1) include in the definition of Complex Areas that the challenges should demonstrably present high complexity and require atypical times for rehabilitation (data indicates it typically takes 15 years in São Paulo); 2) consider as a technical challenge the extensive heterogeneous weathering profile, typical of humid tropical regions; 3) consider as a technical and non-technical challenge the high number of unregistered abstraction wells; 4) consider as a non-technical challenge the existence of social-economic conflicts; 5) evaluate in detail, including with isotopic studies, the possible presence of commingled plumes; 6) progressively develop Temporal Conceptual Models (clear and holistic).